Reconsidering the Role of Food Prices in Inflation - Walsh, James (Washington, D.C. : International Monetary Fund, 2011)
Food prices are generally excluded from measures of inflation most closely watched by policymakers due either to their transitory nature or their higher volatility. However, in lower income countries, food price inflation is not only more volatile but also on average higher than nonfood inflation. Food inflation is also in many cases more persistent than nonfood inflation, and shocks in many countries are propagated strongly into nonfood inflation. Under these conditions, and particularly given high global commodity price inflation in recent years, a policy focus on measures of core inflation that exclude food prices can misspecify inflation, leading to higher inflationary expectations, a downward bias to forecasts of future inflation and lags in policy responses. In constructing measures of core inflation, policymakers should therefore not assume that excluding food price inflation will provide a clearer picture of underlying inflation trends than headline inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet